Technology Of Growing Medicinal Raspberry In The Footmountain Soils Of The Fergana Region - Rajavaliyeva Z.M; Zakirova S.Kh (Zien Journals, 2025)
Barnaul, Vislukha, Progress, oath Marlboro varieties of raspberries, one of the berry fruits grown in our country today, yes been planted oath a high yield of them yes been established
Keywords: Raspberries; seedling; crop; variety